2019
DOI: 10.1002/ajp.23016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary generalists and nutritional specialists: Feeding strategies of adult female blue monkeys (Cercopithecus mitis) in the Kakamega Forest, Kenya

Abstract: Generalist primates eat many food types and shift their diet with changes in food availability. Variation in foods eaten may not, however, match variation in nutrient intake. We examined dietary variation in a generalist-feeder, the blue monkey (Cercopithecus mitis), to see how dietary food intake related to variation in available food and nutrient intake. We used 371 all-day focal follows from 24 adult females (three groups) in a wild rainforest population to quantify daily diet over 9 months. We measured foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…Felton, Felton, Raubenheimer, et al (2009) found that spider monkeys Ateles chamek observed across different phenological periods (seasons) in Bolivia maintained protein intake constant, while allowing NPE to vary with variation in the P:NPE ratio of the diet. The same pattern was observed in blue monkeys Cercopithecus mitis in Kenya (Takahashi et al, 2019), small‐bodied lemurs Lepilemur leucopus in Madagascar (Droscher et al., 2016) and chimpanzees in Uganda (Uwimbimbazi et al, accepted).…”
Section: Discussionsupporting
confidence: 55%
“…Felton, Felton, Raubenheimer, et al (2009) found that spider monkeys Ateles chamek observed across different phenological periods (seasons) in Bolivia maintained protein intake constant, while allowing NPE to vary with variation in the P:NPE ratio of the diet. The same pattern was observed in blue monkeys Cercopithecus mitis in Kenya (Takahashi et al, 2019), small‐bodied lemurs Lepilemur leucopus in Madagascar (Droscher et al., 2016) and chimpanzees in Uganda (Uwimbimbazi et al, accepted).…”
Section: Discussionsupporting
confidence: 55%
“…Horrocks and Baulu's () study also showed preferences for modified habitats and non‐natural foods. Similarly, Takahashi's () study showed clear preferential use by two troops for human‐modified habitat and the non‐natural food resources it provided. One study troop's daily intake of natural foods outweighed that of the other troops, with habitat differences between the home ranges playing an important factor.…”
Section: Discussionmentioning
confidence: 84%
“…In general, larger groups demand larger movement to obtain food resources (Clutton‐Brock & Harvey, ; Borries, Larney, Lu, Ossi & Koenig, ; Pasternak et al, ). However, Takahashi's () study showed group size to be unrelated to movement, with the avoidance of within‐group scramble competition over food being a more important impact on daily foraging movement. Additionally, troop movements correlated with adjustments in diet in response to seasonal food availability within the environment, with regular use of non‐natural, high‐carbohydrate foods found in human‐modified habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could also be facilitated by improving the precision of data collection methods on wild primates through more targeted observational techniques (Melin et al, 2018;Nakagawa, 2009) or the use of technology, such as wearable sensors (Fehlmann et al, 2017;Watanabe & Takahashi, 2014), to capture behaviors related to energy intakes, such as bit rate and foraging behaviors. These techniques could be combined with the experimental presentation of controlled food patches (Marshall et al, 2013), through analyses of wild food patches using geographic information systems (GIS) (Shaffer, 2013), or through detailed nutritional analyses of wild foods (Conklin-Brittain et al, 1998;Johnson et al, 2017;Takahashi et al, 2019;Uwimbabazi et al, 2019). By building knowledge of individual-level foraging strategies, we can gain greater insight into the drivers of primate foraging behavior, better identify when individuals adjust their behavior due to social, ecological, or other constraints, and more accurately estimate the costs individuals experience by foraging in different social and ecological environments.…”
Section: Discussionmentioning
confidence: 99%